Ascorbic Acid Levels in Systemically Healthy Patients with and Without Periodontitis - Ramesh, Amitha; Prakash, Agumbe Priyanka; Ashok, Arya; Thomas, Biju (Journal of Health and Allied Sciences NU, 2017)
Introduction : Periodontitis is a multifactorial disease initiated by plaque. This slowly progressing disease affects the supporting structures of the teeth leading to attachment and bone loss. Nutrition plays an important role in the inflammation and this could be related to effect of nutrition on periodontal disease prevalence. Vitamin C also known as ascorbic acid is abundantly found in fruits and vegetables play a role in the periodontal disease. It can scavenge free oxygen radicals and protect lipid from peroxidation and is a potent antioxidant.Materials and methods : A total of 50 systemically healthy subjects were selected and divided into control group A (25 subjects without chronic periodontitis) and test group B (25 subjects with chronic periodontitis) and blood samples were collected to assess ascorbic acid levels. The data obtained were subjected to statistical analysis.Results : showed statistical significance (p value 0.004) in the ascorbic acid levels between the two groups.Conclusion : The plasma ascorbic acid level was significantly reduced in systemically healthy individuals with chronic periodontitis when compared to systemically healthy without periodontitis which could be attributed to the protective nature of this vitamin in chronic disease like periodontitis.
Keywords: Ascorbic acid; chronic periodontitis; Antioxidant